Oral History Interview: Pioneer Memory Days Railroads in Bakersfield Henry Bock interviewed by Bill Picking - Bock, Henry; Picking, Bill
Henry Bock was born on October 31st, 1890 in Los Angeles, California. He was the son of German immigrants, Ernest Herman Bock and Freda Franka. Bock began working for the Southern Pacific Railroad as a call boy when he was sixteen years old. Over the course of fifty years, Bock worked various jobs on the railroad with train routes that went through Bakersfield, Los Angeles, Fresno, Mojave, Barstow, and Tehachapi. Bock provides details and stories of his experiences working on the railroad during the Great Depression, World War I, and World War II.